Users profile in the counseling service for Special Attention to DST/AIDS Campos Elísios, city of São Paulo,Brasil - Castaldelli Verri Deienno, Marylei; Farias, Norma; Chencinscki, Janice; Nunes Simões, Renata (BEPA. Boletim Epidemiológico Paulista, 2010)
The objective of this study was to describe the users profile of patients attending HIV testing and counseling service in the neighborhood of Campos Eliseos STD/AIDS in São Paulo City, Brazil, and to measure the HIV infection and Syphilis prevalence. Methodology employed a prospective, cross-sectional study of individuals who attended testing and counseling in that site from April to July, 2006. Data from 540 interviews were analyzed. We used descriptive analysis calculated for the following variables: gender, age, race, schooling, marital status, professional situation, area of residence, region of work, reason for seeking the service, origin of the demand, sexual behavior, condom use, exposure/vulnerability, syphilis, and serologic results for HIV and Syphilis Among subjects included in the study ,70% were male, 41% were between 20-29 years of age, 59% were white, 43% had 8-11 years of schooling, 73% were single, 64% and 53% lived and worked in the central area,.15% were sex workers, 75% were tested for HIV, and 76% were tested for VDRL. Men who have sex with men were more than 50% among subjects who attended at the service. There were 403 HIV tests and 408 VDRL tests performed, with 11% of HIV positive tests and 9% of reagent VDRL. The results show that the risk for syphilis and hepatitis is high in MSM. Discussion of this subject is important for decision makers in prevention and care, especially regarding more vulnerable populations.